Carbon footprint analysis of pallet remanufacturing. (10th July 2016) - Tornese, Fabiana; Carrano, Andres L.; Thorn, Brian K.; Pazour, Jennifer A.; Roy, Debjit
Abstract: This research is the first attempt to characterize the carbon equivalent emissions associated with pallet remanufacturing operations for two repositioning scenarios (cross-docking and take-back), and under multiple levels of pallet loading and service conditions. Industry data was acquired through observations and time studies at 12 facilities in North America. Models of pallet component breakdown patterns were used to characterize the carbon equivalent emissions of pallet remanufacturing over the predicted service life. Results show that materials account for the vast majority of remanufacturing operation emissions with three board components responsible for 50–90% of total remanufacturing emissions. The loading and handling environment significantly impacts remanufacturing emissions thus breakeven points where remanufacturing emissions exceed those from newly manufactured pallets are provided for each condition. Also, a pallet-cross-docking policy was shown to reduce emissions when compared to a take-back policy. Finally, a linear optimization model is provided to understand the benefits of preemptive component repair. Results show that preemptive remanufacturing schedules can reduce carbon equivalent emissions by up to 40%. These insights can help guide the pallet industry towards more sustainable pallet management strategies. Highlights: Materials account for the majority of emissions within remanufacturing operations. Three pallet components account for 50–90% of pallet remanufacturing emissions. Loading and handling conditions greatly impact the remanufacturing emissions. Remanufacturing depot location can help reduce CO2 eq. footprint. Preemptive remanufacturing schedules can reduce CO2 eq. emissions by up to 40%.